Le soglie del sé: una comparazione vegetale (Itinera, 2025)
The thresholds of the self: a vegetal comparisonThe article, starting from a satirical quote of a comedy by Aristophanes that starts the reflection, analyzes the concept of sensation of self throughout the history of philosophy, exposes the different positions offered by the numerous authors who have treated it with different theories, and offers a comparison with plants (roses), hypothesizing that reproductive self-incompatibility could be a sort of sketched sensation of self that has allowed the biodiversity of the species. The reason that led to considering the vegetal comparison valid is this. The absence of a nervous system in plants has not in the least denied them some form of “cognition”. And what if this absence “revealed” or was in some way a good starting point to clarify the matter of the self?
Keywords: sensation of self; self-incompatibility; variability; plants